Synthesis and photovoltaic properties of novel ferrocene-substituted metallophthalocyanines - YALÇIN, BAHATTİN; ÖZDEMİR, MÜCAHİT (ROYAL SOC CHEMISTRY, 2022)
In this paper, a series of new metallophthalocyanines, including ferrocene groups, were designed, synthesized and, characterized, and their photovoltaic properties were investigated as alternative electron-donor materials in bulk heterojunction (BHJ) solar cells. These products were synthesized by a Sonogashira cross-coupling reaction between tetraiodophthalocyanine and ethynyl ferrocene. The newly synthesized phthalocyanines (4-6) were characterized by FT-IR, UV-Vis, H-1 NMR, and MALDI-TOF spectroscopic methods and elemental analysis. The electrochemical characterizations were carried out by cyclic voltammetry as well as differential pulse voltammetry. Density functional theory calculations were realized to prove the charge separation between ferrocene as an electron-donor and the phthalocyanine ring as an acceptor. According to UV-Vis measurements, a 25 nm red-shift was observed for complex 4 compared with complexes 5 and 6. Finally, the photovoltaic performance of these compounds used as an electron-donor moiety in a BHJ device were investigated. A function of different blend ratios was tested by fabricating a series of BHJ devices with the architecture of FTO/PEDOT:PSS/4-6: PCBM blend/Ag with an identical thickness of the active layer. The results indicated that the photovoltaic conversion efficiency of BHJ devices exhibited a strong blend-ratio dependence. The maximum power conversion efficiency was obtained by 5-based devices, as 3.65%, with a blend ratio of 1.5 : 1.0 under standard AM 1.5 illumination.
Keywords: PHTHALOCYANINE; EXCHANGE; BLEND; PCBM